Retinal vascular occlusion in pregnancy: three case reports and a review of the literature - L. Jürgens (Journal of Medical Case Reports, 2022)
Abstract Background Retinal arterial occlusive events in young patients are rare. However, because of physiological multifactorial adaptations during pregnancy, retinal vascular occlusive disease may occur spontaneously. In addition, a patent foramen ovale is a risk factor for an ischemic thromboembolic event. Since fluorescein angiography, a central tool in the evaluation of these occlusions, should be avoided during pregnancy, optical coherence tomography angiography, a novel technique, offers a good opportunity for visualizing vascular perfusion of retinal tissue. Case presentation Here we present a case series of three patients (Caucasian, nonsmoker) who visited our clinic owing to acute visual impairment and central scotoma. Using regular optical coherence tomography and optical coherence tomography angiography, retinal vascular occlusions were detected, thus initiating the evaluation of systemic risk factors. We report two patients (30 and 32 years old) who developed cilioretinal artery occlusion but whose etiology differed: one was of thromboembolic origin associated with patent foramen ovale, while the other was caused by hemodynamic blockade secondary to central retinal vein occlusion. In both cases, optical coherence tomography angiography revealed reperfusion of the cilioretinal artery occlusion. However, transient ischemia led to retinal atrophy after a few weeks. In the third patient (32 years old), 8 weeks after onset of scotoma, optical coherence tomography angiography revealed atrophy of the middle layers and impaired perfusion in the deep capillary plexus, and thus a paracentral acute middle maculopathy was diagnosed. All patients regained normal visual acuity and had otherwise uncomplicated pregnancies, and laboratory blood tests did not reveal any defects or alterations. Conclusions As shown here, optical coherence tomography angiography enables risk-free imaging of retinal vessel perfusion during pregnancy. Together with regular optical coherence tomography, it allows one to predict functional outcome according to the existing retinal occlusion-related atrophy.